2021
DOI: 10.1016/j.ijid.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study identifies infection related risk factors in close contacts during COVID-19 epidemic

Abstract: This study aimed to compare the risk of infection of children with that of adults and to explore risk factors of infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) by following up close contacts of COVID-19 patients. Method: The retrospective cohort study was performed among close contacts of index cases diagnosed with COVID-19 in Guangzhou, China. Demographic characteristics, clinical symptoms and exposure information were extracted. Logistic regression analysis was employed to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 34 publications
1
48
4
1
Order By: Relevance
“…Compared with the SAR for 28 studies 12,14,17,27,94 from January to February 2020 (13.4%; 95% CI, 10.7%-16.7%), the SAR was significantly higher for 30 studies 6,7,15,16,19,22,25,26,28,30,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]93 from March to April 2020 (19.4%; 95% CI, 15.2%-24.5%; P = .03) and 15 studies 5,8,10,18,20,21,23,24,29,31,32,35,37,38,40 from July 2020 to March 2021 (31.1%; 95% CI, 22.6%-41.1%; P < .001) but not significantly different from the SAR for 14 studies…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with the SAR for 28 studies 12,14,17,27,94 from January to February 2020 (13.4%; 95% CI, 10.7%-16.7%), the SAR was significantly higher for 30 studies 6,7,15,16,19,22,25,26,28,30,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]93 from March to April 2020 (19.4%; 95% CI, 15.2%-24.5%; P = .03) and 15 studies 5,8,10,18,20,21,23,24,29,31,32,35,37,38,40 from July 2020 to March 2021 (31.1%; 95% CI, 22.6%-41.1%; P < .001) but not significantly different from the SAR for 14 studies…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate factors associated with differences in SAR, we explored attributes of studies from the periods with the lowest and highest household SARs. Among 28 studies 12,14,17,27,94 from January to February 2020 and 15 studies 5,8,10,18,20,21,23,24,29,31,32,35,37,38,40 from July 2020 to March 2021, 6 studies 12,46,54,57,59,62 (21.4%) and 4 studies 8,10,20,23 (25.0%), respectively, reported testing contacts at least twice, 1 study 46 (3.6%) and 3 studies 5,8,23 (18.8%) reported following contacts for longer than 14 days, 1 study 45 (3.6%) and 6 studies 8,23,24,29,37,40 (33.3%) were published as preprints, 21 studies 12,14,27,46,[48][49][50]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children in the lower grade elementary school group had more psychological reactions such as crying easily, complaining, difficulty in keeping calm, and dependency on parents and family than those in other groups. Although children have a lower rate of COVID-19 infection and less severe clinical manifestations compared to adults, psychological problems are more serious in them, especially in younger children [ 10 ]. In addition, we found that children in lower grades had more difficulty in understanding COVID-19 infection and the necessity of restrictions due to COVID-19 compared to older children.…”
Section: Discussionmentioning
confidence: 99%